The evolution of human sleep: Technological and cultural innovation associated with sleep-wake regulation among Hadza hunter-gatherers. Issue 113 (December 2017) - Samson, David R.; Crittenden, Alyssa N.; Mabulla, Ibrahim A.; Mabulla, Audax Z.P.
Abstract: Sleep is necessary for the survival of all mammalian life. In humans, recent investigations have generated critical data on the relationship between sleep and ecology in small-scale societies. Here, we report the technological and social strategies used to alter sleep environments and influence sleep duration and quality among a population of hunter-gatherers, the Hadza of Tanzania. Specifically, we investigated the effects that grass huts, sound levels, and fire had on sleep. We quantitatively compared thermal stress in outdoor environments to that found inside grass hut domiciles to test whether the huts function as thermoregulated microhabitats during the rainy season. Using physiological equivalent temperature (PET), we found that the grass huts provide sleep sites with less overall variation in thermal stress relative to outside baseline environments. We also investigated ambient acoustic measures of nighttime environments and found that sound significantly covaried with sleep-wake activity, with greater sound levels associating with less sleep. Finally, after controlling for ecological variables previously shown to influence sleep in this population, fire was shown to neither facilitate nor discourage sleep expression. Insofar as data among contemporary sub-tropical foragers can inform our understanding of past lifeways, we interpret our findings as suggesting that after the transition to full time terrestriality, it is likely that early Homo would have had novel opportunities to manipulate its environments in ways that could have significantly improved sleep quality. We further conclude that control over sleep environment would have been essential for migration to higher latitudes away from equatorial Africa.